Revealing the Critical Role of Titanium in Layered Manganese‐Based Oxides toward Advanced Sodium‐Ion Batteries via a Combined Experimental and Theoretical Study. Issue 4 (30th August 2018) - Fang, Tiancheng; Guo, Shaohua; Jiang, Kezhu; Zhang, Xiaoyu; Wang, Di; Feng, Yuzhang; Zhang, Xueping; Wang, Peng; He, Ping; Zhou, Haoshen
Abstract: Sodium‐ion batteries are one of the most promising candidates for large‐scale energy storage. Manganese‐based layered oxides are extensively studied as a cathode of sodium‐ion batteries due to the low cost and high electrochemical activity. However, these layered cathodes usually suffer from the severe manganese dissolution originated from Jahn–Teller distortion, thereby leading to severe capacity fading and structural deterioration. Herein, it is demonstrated via a combined experimental and theoretical study, titanium substitution in layered manganese‐based oxides can weaken the Jahn–Teller effect, minimize the relative dissolution, and thus enable robust sodium storage during long‐term operation. Results reveal that Ti‐doping can restrain shrinkage or elongation of the MnO octahedral structure to minimize the Jahn–Teller distortion for Mn atoms surrounded by titanium. Consequently, P2‐Na0.86 Co0.475 Mn0.475 Ti0.05 O2 can deliver a reversible capacity over 110 mAh g −1, good rate capability, and superior long‐cycling performance (81.1% cycle retention after 200 cycles at high rate of 5 C). The findings provide new opportunities for design of high‐performance electrodes for sodium‐ion batteries and deepen the understanding of intercalation chemistry in layered structures. Abstract : Ti‐doped manganese‐based layered oxide sodium‐ion battery cathode (P2‐Na0.86 Co0.475 Mn0.475 Ti0.05 O2, NCMT is proposed, which can suppress the Jahn‐Teller effect of manganese and minimize the manganese dissolution. Density functional theory calculations disclose the Ti‐doping can depress the shrinkage or elongation of the Mn‐O bond in the octahedral structure. Moreover, the results show NCMT exhibits better electrochemical performance compared to the non‐Ti doped analog.